Rehabilitation of torture survivors and prevention of torture: Priorities for research through a modified Delphi Study (with Commentaries) - Pau Pérez-Sales; Nicola Witcombe; Diego Otero Oyague (Torture)
Background: Research is a key element in prevention and in ensuring that survivors of torture have access to appropriate and effective rehabilitation, but it is often neglected as more pressing issues frequently come first.